Clustering supermarkets: the role of experts - Armando B. Mendes; Cardoso, M. G. M. S. (Journal of Retailing and Consumer Services, 2006)
This work is part of a supermarket chain expansion study and is intended to cluster the existent outlets in order to support the evaluation of outlet performance and new outlet site location. To overcome the curse of dimensionality (a large number of attributes for a very small number of existing outlets) experts’ knowledge is considered in the clustering process. Three alternative approaches are compared for this end, the experts being required to: (1) a priori: provide values for perceived dissimilarities between pairs of outlets; (2) a posteriori: evaluate results from alternative regression trees; (3) interactively: help to select base variables and evaluate results from alternative dendrograms. The later approach provided the best results according to the marketing experts.